1997
DOI: 10.1159/000189581
|View full text |Cite
|
Sign up to set email alerts
|

Six Novel Mutations in the Vasopressin V2 Receptor Gene Causing Nephrogenic Diabetes insipidus

Abstract: X-linked nephrogenic diabetes insipidus (NDI) is a rare disease caused by mutations in the vasopressin V2 receptor (AVPR2) gene. We analyzed the AVPR2 gene in 6 unrelated Korean families with X-linked NDI, and found 6 novel mutations. Two of them were missense point mutations, 2 were short deletions causing frameshifts, 1 was a duplication of 9 bases, and 1 was a compound gene rearrangement. Four mutations cosegregated with the clinical phenotype in corresponding family members, and one was a de novo mutation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…This pattern has been reported in other studies, regardless of the origin of the populations [10,43,50]. Importantly, the complete genetic study revealed nine not previously reported AVPR2 mutations: p.Ser54Arg, p.Tyr117*, p.Ala140Thr, p.Ser171Alafs*24, p.Trp200Glyfs*12, p.Ala216Aspfs*55, p.Cys283Tyr, Intracellularly retained protein mainly in the endoplasmic reticulum [34,44].…”
Section: Discussionsupporting
confidence: 82%
“…This pattern has been reported in other studies, regardless of the origin of the populations [10,43,50]. Importantly, the complete genetic study revealed nine not previously reported AVPR2 mutations: p.Ser54Arg, p.Tyr117*, p.Ala140Thr, p.Ser171Alafs*24, p.Trp200Glyfs*12, p.Ala216Aspfs*55, p.Cys283Tyr, Intracellularly retained protein mainly in the endoplasmic reticulum [34,44].…”
Section: Discussionsupporting
confidence: 82%
“…AVPR2 [Cheong et al, 1997] genes. The mutation in the IGHMBP gene comprises the following rearrangement: a deletion of 1737 bp plus an intervening wild-type sequence of 302 bp plus an inversion of 66 bp plus a deletion of 2580 bp.…”
Section: Inversions That Occur In a More Complicated Contextmentioning
confidence: 99%
“…Congenital nephrogenic diabetes insipidus (NDI) is a rare inherited disorder characterized by the insensitivity of the kidney to the antidiuretic effect of vasopressin (1). It is distinguished from neurohypophyseal diabetes insipidus by the lack of response to exogenous vasopressin (2).…”
Section: Introductionmentioning
confidence: 99%